ASURANSI PERTANIAN DALAM PERSPEKTIF MAQASHID SYARIAH: IMPLEMENTASI DAN URGENSI - Netta Agusti; Ihsan Rahmat (Saqifah: Jurnal Hukum Ekonomi Syariah, 2022)
As one of the famous agrarian countries. business potential in the agricultural sector in Indonesia is quite large and very potential when viewed from the geographical conditions of the environment. However, uncertain climatic conditions can be fatal for farmers in their business. Crop failure is a frightening specter for farmers, because it will cause financial losses. Through government programs regulated in Law Number 19 of 2013 concerning the protection and empowerment of farmers, the government seeks to protect farmers, one of which is through the policy of having an agricultural insurance program. This paper aims to see how the concept and application of agricultural insurance is related to the maqashid sharia concept. Protection against risk is as important as other basic needs because it is expected to ensure continuity of fulfillment of needs in one's life. From an Islamic point of view, this fulfillment is categorized into five main areas as determined by the maqashid sharia, namely the demands of maintaining religion, reason, soul, children, and property so that the objectives of sharia are achieved.